Critical‐sized full‐thickness skin defect regeneration using ovine small intestinal submucosa with or without mesenchymal stem cells in rat model. Issue 6 (20th October 2017) - Rashtbar, Morteza; Hadjati, Jamshid; Ai, Jafar; Shirian, Sadegh; Jahanzad, Issa; Azami, Mahmoud; Asadpuor, Shiva; Sadroddiny, Esmaeil
Abstract: Decellularized extracellular matrices (ECM) based materials are routinely used for a variety of clinical applications. Hereof, in vivo application of decellularized ovine small intestinal submucosal (DOSIS) layer as, a scaffold is yet to be investigated. In this study, the effectiveness of the DOSIS scaffold, with or without rat bone marrow mesenchymal stem cells (BM‐MSCs), in full‐thickness wound healing of critical‐sized defect was experimentally studied in a rat model. The experimental groups included; group I (control), group II (DOSIS), and group III (BM‐MSCs‐seeded DOSIS). Wound healing of all groups was examined and compared clinically and histopathologically on days 7, 14, and 21 postoperation. Our results represented BM‐MSCs‐seeded DOSIS accelerated wound contraction and healing compared to both the DOSIS alone and control groups. Epithelization was close to completion 21 days postoperation in DOSIS alone. In OSIS with BM‐MSCs group, epithelization was faster and had fully taken place at the subsequent time points. DOSIS layer, as cell‐free form with low substantially DNA content, accelerated healing of rat skin wound defects that was created at critical‐size and full‐thickness. In conclusion, decellularized OSIS alone and in combination with BM‐MSCs has the potential to be used as a wound graft material in skin regenerative medicine. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 2177–2190, 2018.